Marketplace and E-commerce Training as a Student Entrepreneurship Practice Container - Supatminingsih, Tuti; Tahir, Thamrin; Ahmad, Muhammad Ihsan Said; Balki, Syarifah; Esso, Andi Sawe Ri (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2025)
This Community Partnership Program (PKM) aims to improve students' digital entrepreneurship literacy through training in the use of marketplaces and e-commerce as a medium for business practice. This activity is motivated by the increasing need for technology-based entrepreneurial competencies in the digital era, where students need to be equipped with the ability to market products boldly. The training is conducted through interactive lectures, reflection, and hands-on practice in creating online stores on designated marketplace platforms. Students are guided from an introduction to e-commerce concepts, product upload techniques, compiling product descriptions, determining prices, and simple digital promotion strategies. The results of the activity indicate that students are able to understand the marketplace workflow and can create digital stores independently. Students also demonstrated increased creativity in preparing marketing materials, while gaining practical experience in marketing products online. Overall, this PKM has a positive impact on building digital entrepreneurship skills and increasing students' motivation to utilize e-commerce platforms as a means of business development. This program is recommended for ongoing implementation to strengthen students' digital competencies and support entrepreneurship-based learning in schools.